2017
DOI: 10.1016/j.eats.2017.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Lesser Trochanter Osteoplasty for Ischiofemoral Impingement

Abstract: Ischiofemoral impingement is a newly recognized cause of extra-articular hip pain, and is caused by contact between the lesser trochanter and ischium. Surgical intervention has been proven successful for patients with persistent pain and disability after failure of nonoperative management. This technique article provides a reliable method for endoscopic lesser trochanter osteoplasty using an anterior approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Ischiofemoral impingement syndrome usually occurs after conservative treatment of trochanter minor fractures; therefore, it is important to keep this potential complication in mind during long-term follow-ups. [5,6] Recent studies have indicated that a considerable proportion of trochanter minor fractures in young patients exhibit complete healing within approximately one year, without any detectable deformities upon clinical examination. Jason Mascoe and his colleagues indicated in their study that patients with non-displaced trochanter minor fractures are treated non-surgically with successful results.…”
Section: Discussionmentioning
confidence: 99%
“…Ischiofemoral impingement syndrome usually occurs after conservative treatment of trochanter minor fractures; therefore, it is important to keep this potential complication in mind during long-term follow-ups. [5,6] Recent studies have indicated that a considerable proportion of trochanter minor fractures in young patients exhibit complete healing within approximately one year, without any detectable deformities upon clinical examination. Jason Mascoe and his colleagues indicated in their study that patients with non-displaced trochanter minor fractures are treated non-surgically with successful results.…”
Section: Discussionmentioning
confidence: 99%
“…Lesser trochanter resection can also be successfully performed endoscopically, as previously described by several authors. [18][19][20][21][22] Several complications have been reported with the endoscopic approach, including temporary sciatic nerve injury, hematoma, permanent nerve injury of the posterior femoral cutaneous nerve, 23 and intra-abdominal fluid extravasation. 24 This method does incur a steeper learning curve as well as less direct visualization of the important surrounding neurovascular structures; consequently, entrapment of the sciatic nerve is the leading reported cause of revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, external rotation of the hip allows for improved access to the posterior aspect of the lesser trochanter. However, an iliopsoas tenotomy is necessary to gain access to the entirety of the lesser trochanter 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Hatem et al 13 highlighted that an advantage of this approach was that a majority of the iliopsoas tendon remains attached to the lesser trochanter. Meanwhile, Goodwin et al 14 described an endoscopic technique of performing lesser trochanterplasty using an anterior approach 14 , avoiding the medial femoral circumflex artery, sciatic nerve, and disruption of the quadratus femoris muscle. In addition, external rotation of the hip allows for improved access to the posterior aspect of the lesser trochanter.…”
Section: Discussionmentioning
confidence: 99%